2014
DOI: 10.1017/s0967199414000628
|View full text |Cite
|
Sign up to set email alerts
|

Is the interchromosomal effect present in embryos derived from Robertsonian and reciprocal translocation carriers particularly focusing on chromosome 10 rearrangements?

Abstract: The aim of this study was to analyse the possible occurrence of the interchromosomal effect (ICE) in human preimplantation embryos obtained from Robertsonian and reciprocal translocation carriers focusing on ones with chromosome 10 rearrangements who were undergoing preimplantation genetic diagnosis (PGD) and to investigate whether offering aneuploidy screening would be beneficial to these patients. Cleavage stage embryos from translocation carriers undergoing PGD were biopsied. Multicolour fluorescence in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…However, the interchromosomal effect (ICE) may exist in varying degrees depending on the individual rearrangement. Several controversial studies have shown that ICE may present in oocytes ( 42 44 ) and cleavage-stage embryos and blastocysts ( 45 , 46 ), and the occurrence of ICE has related to the region of the translocation and the position of breakpoints ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the interchromosomal effect (ICE) may exist in varying degrees depending on the individual rearrangement. Several controversial studies have shown that ICE may present in oocytes ( 42 44 ) and cleavage-stage embryos and blastocysts ( 45 , 46 ), and the occurrence of ICE has related to the region of the translocation and the position of breakpoints ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Tulay et al [21] found no statistically significant difference in the malsegregation rate between 495 embryos obtained from the carriers of translocations (RobT and reciprocal) and from the 1284 embryos from the control group; therefore, there is no evidence for ICE. Xie et al [22] also did not found evidence of ICE in 1214 cleavage and blastocyst stage embryos obtained from reciprocal and RobT carriers.…”
Section: Discussionmentioning
confidence: 94%
“…Pinar et al investigated cleavage-stage embryos from translocation carriers undergoing PGD, which were biopsied by mFISH for the chromosomes involved in the translocation in addition to chromosomes13, 15,16,17,18,21,22, X, and Y. They found no ICE in embryos derived from Robertsonian and reciprocal translocation carriers [30]. The mechanism for how the translocation chromosomes disrupted other noninvolved chromosomes in embryogenesis was not defined clearly.…”
Section: Discussionmentioning
confidence: 99%